Technical Difficulties and Related Control Strategies on In-Depth Peak Regulation for Supercritical Circulating Fluidized Bed Boiler - Pengcheng WANG; Boyu DENG; Jin CAI; Ke WANG; Hao KONG; Lifeng LI; Man ZHANG; Hairui YANG (Zhongguo dianli)
In order to further improve the stability and economy of the operation of supercritical circulating fluidized bed (CFB) boiler units in the process of deep peak regulation, this paper takes the 350 MW supercritical CFB boiler of a power plant as the research object and proposes the corresponding control strategies and technical measures based on the analysis of the series of problems in deep peak regulation, such as steady combustion and fluidization, hydrodynamic safety, steam feed pump control, emission control, and so on. The practical operation results show that by adopting these control strategies, long-term steady operation of the boiler can be achieved. The research results can provide helpful reference for the deep peak regulation of supercritical CFB boilers of the same type and even the ultra-supercritical CFB boilers.